Influence of respiratory disease experiences on COVID-19 vaccine acceptance: a study from Southeastern Louisiana - Saba Barri; Sara Al-Dahir; Klaus Heyer; Ashley Taylor; Alaa Khalil; Mohamed Belkhouche; Brooke-Ashleigh Bonvillain; Kathryn Caldwell; Heather Surcouf; Ibrahim Hamed; Malack Jwayyed; Leslie S. Craig; et al. (Frontiers in Public Health)
IntroductionRespiratory diseases, including influenza (flu) and respiratory syncytial virus, continue to be major health concerns globally. The onset of COVID-19 further compounded these issues, making it important to examine public attitudes toward vaccination and understanding of respiratory diseases. This study explores factors influencing decisions to receive the latest COVID-19 vaccine, focusing specifically on the role of prior respiratory illness diagnosis.MethodsA follow-up survey among 299 participants from Southeastern Louisiana across 10 healthcare facilities was administered via phone and the Qualtrics platform, gathering information about the likelihood of receiving the latest COVID-19 vaccine. Quantitative data were analyzed using log-binomial and Poisson regression models to assess relationships between respiratory illness history and COVID-19 vaccine acceptance.ResultsNearly half (47%) of the participants reported a history of respiratory illness. Individuals with prior respiratory diagnosis were more likely to accept the latest COVID-19 vaccine (62%) than those without (41%) (RR: 1.79, 95% CI: 1.26–2.56). In fully adjusted models, accounting for age, prior vaccine hesitancy, and comorbidities, influenza vaccine acceptance (RR: 1.87, 95% CI: 1.06–3.28) was associated with greater likelihood of receiving the latest COVID-19 vaccine. Key barriers to vaccination, including concerns about side effects and distrust in vaccine efficacy were identified.DiscussionParticipants with respiratory illnesses and those with positive vaccination histories, particularly regarding influenza, showed a higher likelihood of accepting the latest COVID-19 vaccines. However, significant obstacles to vaccine uptake persist. Tailored public health efforts that address these concerns are crucial to improving vaccine rates, particularly among hesitant groups.